Causality Relationship between the Development of the Oil and Gas Sector and Foreign Investments - Huseynli, Bahman (International Journal of Energy Economics and Policy, 2023)
In this study on Azerbaijan, which is dependent on oil, the causality relationship between economic growth, foreign investments, total capital increases in the country and oil and gas sector revenues have been examined. As a result of the analysis made using the Granger method, a row of causality relationships was obtained. The data used in the analysis were obtained from the World Bank, an important data disclosure platform. The result of the analysis made for a period from 2000 to 2020 shows the importance of the oil and gas sector in attracting foreign investments in this country. As a result of the study, a bidirectional causality relationship was obtained between economic growth and foreign investments in Azerbaijan. In other words, while attracting foreign investments to the country supports economic growth, the realization of economic growth at the same time shows its own effect on the growth of the country’s economy. Namely, these variables become the Granger causality of each other. Bilateral causality relationship has also been determined between foreign investments and the incomes obtained from the total oil and gas sector. At the same time, the development of this sector makes the country more attractive for foreign investors. Increases in revenues in the oil and gas sector also have an impact on the overall capital increase in the country. In other words, this variable is the Granger cause of capital increases.